Associations of Height With the Risks of Colorectal and Endometrial Cancer in Persons With Lynch Syndrome. Issue 2 (17th August 2020) - Brouwer, Jesca G M; Newcomb, Polly A; Bisseling, Tanya M; Figueiredo, Jane C; Hopper, John L; Jenkins, Mark A; Koornstra, Jan J; Lindor, Noralane M; Vasen, Hans F A; Win, Aung K; Kampman, Ellen; van Duijnhoven, Fränzel J B
Abstract: People with Lynch syndrome (LS), who carry a pathogenic mutation in a DNA mismatch repair gene, have increased risks of colorectal cancer (CRC) and endometrial cancer (EC). A high reported variability in cancer risk suggests the existence of factors that modify cancer risk for persons with LS. We aimed to investigate the associations between height and CRC and EC risk for persons with LS using data from 2 large studies. Information on 1, 115 men and 1, 553 women with LS from the Colon Cancer Family Registry (1998–2007) and the GEOLynch Cohort Study (2006–2017) was harmonized. We used weighted Cox proportional hazards regression models with age on the time axis to estimate adjusted hazard ratios and 95% confidence intervals for each 5-cm increment in self-reported height. CRC was diagnosed in 947 persons during 65, 369 person-years of observation, and 171 women were diagnosed with EC during 39, 227 person-years. Height was not associated with CRC for either men (per 5-cm increment, hazard ratio (HR) = 1.00, 95% confidence interval (CI): 0.91, 1.11) or women (per 5-cm increment, HR = 1.01, 95% CI: 0.92, 1.11), nor was height associated with EC (per 5-cm increment, HR = 1.08, 95% CI: 0.94, 1.24). Hence, we observed no evidence for an association of height with either CRC or EC among persons with LS.